2012
DOI: 10.15835/buasvmcn-agr:8689
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mineral Fertilization upon the Floristical Composition of the Mountain

Abstract: The administration of large quantities of chemical fertilizers may strongly diminish the plant diversity of semi-natural grasslands. In the Apuseni Mountains (Romania), the chemical fertilization is rarely used, but, considering the population’s decrease and the livestock diminish, this might have a greater importance in the future. The maintenance of semi-natural grasslands within the mountainous landscape depends greatly on fertilization. Our paper’s goal is to assess the influence of mineral fertilizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study similar to ours found that the specific richness of a grassland included 38 plant species in the control variant and that the natural grasslands have a moderate floristic biodiversity, and by applying the treatments, the specific richness will be reduced simultaneously with the dose of manure applied, results also confirmed by our studies [ 37 ]. Another study conducted in 2007, in the context of long-term experiments in the Czech Republic, found that the application of low-dose manure has significantly contributed to improving and maintaining the number of plant species in the vegetal cover [ 38 ]. This aspect is also confirmed by our results in the variant with 10 t ha −1 manure, where there was a minor change in the floristic composition.…”
Section: Discussionmentioning
confidence: 99%
“…A study similar to ours found that the specific richness of a grassland included 38 plant species in the control variant and that the natural grasslands have a moderate floristic biodiversity, and by applying the treatments, the specific richness will be reduced simultaneously with the dose of manure applied, results also confirmed by our studies [ 37 ]. Another study conducted in 2007, in the context of long-term experiments in the Czech Republic, found that the application of low-dose manure has significantly contributed to improving and maintaining the number of plant species in the vegetal cover [ 38 ]. This aspect is also confirmed by our results in the variant with 10 t ha −1 manure, where there was a minor change in the floristic composition.…”
Section: Discussionmentioning
confidence: 99%